Modelling air standard thermodynamic cycles using python. (October 2022) - Dumka, Pankaj; Rana, Kritik; Tomar, Surya Pratap Singh; Pawar, Parth Singh; Mishra, Dhananjay R.
Highlights: Air standard cycles are modelled. In-depth algorithm has been presented for code writing. Python programming has been used to model the cycles. Developed python codes have been presented. The results of computer program agree with the analytical results. Abstract: In this research article, an attempt has been made to model gas power cycles (Carnot, Otto, Diesel, Dual, Atkinson, Lenoir, Stirling, and Ericsson). The thermodynamic modelling of the processes has been done in the python. A detailed algorithm for each cycle is developed and implemented via python programs. The pressure and volume at each state for different processes were obtained and plotted in p-v diagrams. The results of the program developed have shown good agreement with the literature. The developed code can also be extended for any other thermodynamic cycle.